Low-Frequency Oscillation Suppression Strategy forGrid-Forming Converters Based on Active-Power-LoopVirtual Damping Control (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
With the rapid growth of renewable energy penetration, grid-formingconverters (GFMs) have become essential for the stable operation of new powersystems. However, the virtual synchronous generator (VSG) features strongcoupling between power and voltage-current control loops due to powerelectronic multi-timescale dynamics, which easily induces negative dampingand low-frequency oscillations (LFOs). Under the commonly adopted constantDC-voltage assumption, the interactions among the active-power and reactivepower loops, together with the influence of the fast voltage-current controlloops, may still result in insufficient damping and LFO. To solve this issue, thispaper proposes a virtual damping control (VDC) strategy for the active powerloop. A reduced-order small-signal model considering the coupling between theactive-power and reactive-power loops is established, while the voltage-currentinner-loop dynamics are neglected under the assumption that they are muchfaster than the outer-loop dynamics. A VDC scheme employing band-passfiltering and phase compensation is designed to generate supplementary powermodulation, providing damping torque to suppress oscillations. Eigenvalueanalysis and time-domain simulations validate the proposed method. Comparedwith traditional virtual impedance (VI) control, the proposed VDC effectivelysuppresses LFO and improves the damping performance and dynamic stabilityof the GFM system
Keywords: Grid-Forming; Virtual synchronous generator; Low-frequency oscillation; Virtual damping control; Active power loop